o-Carborane, Ferrocene, and Phthalocyanine Triad for High-Mobility Organic Field-Effect Transistors - Nar, Ilgin; Atsay, Armagan; Altindal, Ahmet; Hamuryudan, Esin (AMER CHEMICAL SOC, 2018)
An unsymmetrical zinc phthalocyanine with ferrocenylcarborane linked to the phthalocyanine ring through a phenylethynyl spacer was designed for organic field-effect transistor (OFET). The unsymmetrical phthalocyanine derivatives were characterized using a wide range of spectroscopic and electrochemical methods. In particular, the ferrocenylcarborane structure was unambiguously revealed based on the single-crystal X-ray diffraction analysis. In-depth investigations of the electrochemical properties demonstrated that the ferrocenylcarborane insertion extended the electrochemical character of ferrocenylcarborane-substituted phthalocyanine (7). Moreover, in the anodic potential scans, the oxidative electropolymerization of etynylphthalocyanine (6) and 7 was recorded. To clarify the effect of the insertion of ferrocenylcarborane (2) on the field-effect mobility, solution-processed films of 2, 6, and 7 were used as an active layer to fabricate the bottom-gate top-contact OFET devices. An analysis of the output and transfer characteristics of the fabricated devices indicated that the phthalocyanine derivative functionalized with ferrocenylcarborane moiety has great potential in the production of high-mobility OFET.
Keywords: THIN-FILM TRANSISTORS; OFET PROPERTIES; SUBSTITUTED METALLOPHTHALOCYANINES; PHOTOPHYSICAL PROPERTIES; CHARGE-TRANSPORT; RECENT PROGRESS; ELECTRONICS; BEHAVIOR; AROMATICITY; MONOLAYERS; Chemistry